2020
DOI: 10.2147/dddt.s230459
|View full text |Cite
|
Sign up to set email alerts
|

<p>Suitability of Amoxicillin–Clavulanic Acid for Administration via Prolonged Infusion</p>

Abstract: Rationale: Previously, we have been able to outpace bacterial mutation by replacing increasingly ineffective antibiotics with new agents. However, with the discovery of new antibiotics diminishing, optimising the administration of existing broad-spectrum antibiotics such as co-amoxiclav has become a necessity. Methods: A stability indicating HPLC method was developed and validated in compliance with International Council for Harmonisation (ICH) guidelines. Stability of co-amoxiclav at clinical concentration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Amoxicillin and clavulanic acid solutions retained more of their initial concentration for longer than reported in previously published results where they were prepared in combination. 11 The slopes of the regression lines for both active pharmaceutical ingredients (APIs) at the three temperatures studied showed significant deviation from zero at the 99% level of confidence, indicating amoxicillin and clavulanic acid exhibit degradation with time ( Table 1 ). Similarly, to previously published data, 11 ANCOVA showed that solutions stored at lower temperatures remained stable for significantly longer than solutions at higher temperatures ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Amoxicillin and clavulanic acid solutions retained more of their initial concentration for longer than reported in previously published results where they were prepared in combination. 11 The slopes of the regression lines for both active pharmaceutical ingredients (APIs) at the three temperatures studied showed significant deviation from zero at the 99% level of confidence, indicating amoxicillin and clavulanic acid exhibit degradation with time ( Table 1 ). Similarly, to previously published data, 11 ANCOVA showed that solutions stored at lower temperatures remained stable for significantly longer than solutions at higher temperatures ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 11 The slopes of the regression lines for both active pharmaceutical ingredients (APIs) at the three temperatures studied showed significant deviation from zero at the 99% level of confidence, indicating amoxicillin and clavulanic acid exhibit degradation with time ( Table 1 ). Similarly, to previously published data, 11 ANCOVA showed that solutions stored at lower temperatures remained stable for significantly longer than solutions at higher temperatures ( Table 2 ). The influence of temperature of both APIs is displayed in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged infusions of antibiotics are already under study and have shown promising results. 13,14 There are, however, some key challenges to address for this scheme to be successfully implemented.…”
Section: Pragmatic Approaches For Cancer Care Continuummentioning
confidence: 99%